Exploring the in situ Utilization of Cyclic Imine Intermediates Generated by Isocyanoacetate Cycloaddition: Convergent Assembly of cis‐3a, 8a‐Hexahydropyrrolo[2, 3‐b]indole Scaffolds. Issue 11 (31st July 2014) - Huang, Lin; Cheng, Hengguang; Zhang, Runmei; Wang, Min; Xie, Chunsong
Abstract Under copper(I) or silver(I)/base cocatalysis conditions, transient 2H‐pyrroline intermediates generated by the cycloaddition of isocyanoacetates and olefins can be in situ subjected to further transformations. A strategically novel, convergent, mild, efficient, general and atom‐economic access to cis‐3a, 8a‐hexahydropyrrolo[2, 3‐b]indoles, which are core scaffolds in many biologically important natural products, has been developed based on this concept. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>